ANALYSIS OF CLICKS AND BRICKS: CONSUMERS’ ATTITUDE TOWARDS ONLINE STORE AND TRADITIONAL STORE OF CHARLES & KEITH CONSUMER IN MANADO - Sendow, Fiorentina F.; Pangemanan, Sifrid S.; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2019)
Abstract: Marketing is one of the key factors in the success of a company’s business. This is because marketing is the activity, set of institutions and process for creating, communicating, delivering and exchanging offerings that have values for customers, clients, partners and society at large. Marketing have an important role in deciding the consumers’ attitude in buying behavior. Consumers’ attitude towards online store is different with consumers’ attitude towards traditional store. This study aims to analyze the consumers’ attitude towards online store and traditional store of Charles & Keith consumer in Manado. This research uses qualitative method with interview used to collect the data. The population in this research refers to the consumers of Charles & Keith in Manado with samples 15 of Charles & Keith consumer, which were chosen through purposive sampling. The results showed the indicators of the consumers’ attitude towards online store or traditional store that affects to their behavior to buy. It is recommended for Charles & Keith to keep improving their service in store and website or application and the quality of the products in order to keep the consumer loyalty.Keywords: marketing, consumer attitude, consumer behavior, e-commerce, traditional store